Human perception and adjustment to flood hazards: the Kelantan drainage basin experience - Abd Rahim Md Nor; Jamaluddin Md. Jahi (Environmental Management Society, Malaysia, 2000)
Flood represents some degree of hazards to human population. The notion of hazard is one that only makes sense in terms of an evaluation of the earth as a home for the human beings because in its natural form without the present of men flood is just a harmful natural process. This paper is concerned about flood in the State of Kelantan, Peninsular Malaysia, with particular emphasis on how affected people response to this natural hazard. Frequently, floods in this State take longer times to withdraw, cover larger areas and cause a lot more damages to life and properties compared with other areas in the peninsular. During 1981-1998 there were a total of 16 major flood events recorded in the State, the highest in the country. There are some 717 flood-prone villages in this State. This paper is attempt to look into the ways flood hazards in Kelantan affect the life and well beings of the population. A preliminary survey on 800 residents was carried out in the State recently. It was found that when a major flood occurred on average 74.8 percent said that they were unable to go to work while the children were denied from school. On average 78.2 percent of the residents interviewed mentioned t5hat road cutoff is common during flood seasons and 39.8 percent admitted that disruption in electricity supply to their villages is also common. Most of the surveyed residents were unfavorable towards the idea of relocation in response to recurrent flood. Instead, they preferred to stay on the land where are staying now, and wait for the flood to come at the end of the year during Monsoon season. From the total Mukims surveyed, an average of 65.7 percent believed that improving existing houses and renovating it from wood to brick was seen as the best solution in their struggle to avoid hazards posed by flood